Analisis Indeks Pencemaran Air Limbah ke Badan Air Permukaan Pada Sungai Sidoarjo Akibat Pengaruh Industri Tekstil Benang - Rizka Novembrianto; Muhammad Alvando Rahmantio (Prosiding ESEC, 2023)
Waste pollution is a serious problem facing the environment due to human activities, including household and industrial waste. Domestic waste originates from households and public facilities, while industrial waste is generated by various industrial sectors. Mixing domestic and industrial waste can create a pollution index that measures the level of environmental pollution. The pollution index is an important tool in monitoring water and environmental quality, helping to assess the impact of waste on aquatic ecosystems. This research aims to develop a pollution index that combines domestic and industrial waste components. Pollution parameters such as BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), TSS (Total Suspended Solid), DO (Dissolved Oxygen), Total Coliform and pH were measured in water samples. The pollution index is calculated based on the measured parameter values, with a certain weight for each parameter based on the level of impact on the environment. The research results show that there is a relationship between industrial activities and the level of environmental pollution. Although domestic waste generally contributes to parameters such as BOD, COD, pH, TSS, Total Coliform, industrial waste has a significant effect on pollutant content in aquatic environments. The proposed pollution index is able to identify sources of pollution more accurately so as to enable more effective mitigation efforts.